Delivering Counsellor Training to First Nations: Emerging Issues - Hogan, Emmett P.; Barlow, Constance A. (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper reports on the preliminary findings of a review of the outcomes of counsellor training programs on two First Nations communities in southern Alberta. Two general themes emerged as prevalent, namely, the continuing influence of the past, and the struggle for cultural survival. This study has indicated that significant modifications are required to the curriculum delivered. However, the data challenge the assumption of a deficit in the relevance and quality of counsellor training provided to First Nations students, suggesting cause for optimism and ongoing collaboration in counsellor education and training between post-secondary institutions and First Nations communities.